Trigger system for a large area RPC TOF-tracker - Clemencio, Filomena (2019)
The TOF-tracker concept, the simultaneous measurement of accurate time and bi-dimensional space coordinates in a single gaseous detector, has been previously demonstrated. Recently, a larger area, 1550×1250 mm 2 , RPC detector has been constructed. Signals are induced in metallic strips located in each side of the RPC active volume and coupled to both charge-sensitive and timing circuits, that can be used to generate a coincidence trigger. In this work, the architecture and performance of the trigger system of the detector is reported. The system is based on off-the-shelf inexpensive modules and in a custom program written in VHDL running in a Xilinx Spartan-6 FPGA. It is fast, fully parameterized and supports several trigger strategies, allowing at the same time the collection of several information referring to the operating condition of the detector, relevant for tests and detector maintenance.